PENGARUH SISTEM PENGENDALIAN INTERN, PENGELOLAAN KEUANGAN DAERAH DAN KOMITMEN ORGANISASI TERHADAP PENERAPAN GOOD GOVERNMENT GOVERNANCE (Studi Kasus pada Satuan Kerja Perangkat Daerah Kota Pekanbaru) - Jalius, M Fajri; Rasuli, M; L, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The study aimed to examine the effect of the intern control system, local financial management and organization commitment on the implementation of good government governance of local government in Pekanbaru City. It was a quantitive research utilizing a primary data which were obtained from questionnaire. The population of the study involved all units of local devices found in Pekanbaru city. The selection of the sample used purposive sampling methods with the characteristics of employees who perform the function of accounting / financial administrators, power users budget and budget users. There were about 96 respondents selected as the samples of the study, consisting of Chief SKPD, Secretary and Head of finance in each SKPD Pekanbaru City. The data were analyzed by using a multiple regression. The results of this study found that the intern control system, local financial management and organization management has positive significant effect on the implementation of good government governance with significant < 0.05.Keyword: Intern Control System, Local Financial Management, Organization Commitment and Good Government Governance